Design of factory personnel safety and protection location system based on TDOA technology - Hu Zifei; Wen Guojun; Liang Jingpu; Xia Yu (Dianzi Jishu Yingyong, 2018)
Aiming at the problems such as a great amount of personnel in large modern factory, complicated management of complex company types and frequent accidents, a design scheme of factory security and protection positioning system which can accurately locate all personnel and prevent dangerous risks between people and machinery is put forward. The system is based on high-precision TDOA positioning technology to achieve the staff positioning, dangerous area of virtual alert, plant space division，camera linkage and other advance warning control functions. In personnel management and safety in production, it makes the managers get the knowledge of personnel access information and work conditions compatible with the modern camera monitoring system in the factory. By the terminal early warning control system, the managers receive dangerous warning information in time which can control the accident in advance. This system can be used in the security and protection system of the modern large-scale factory because it could stably combine the monitoring system to realize the camera linkage, and adjust the video monitoring equipment according to the positioning information. What′s more, the visual analysis algorithm of the system is able to analyze various unsafe states in the monitoring screen to efficiently reduce the rate of accident and improve the management efficiency.